Political participation of women in Algeria (1962 - the present day) - مذكور, نورالدين; بوخلخال, عبد الجبار (مجلة الباحث للدراسات الأكاديمية, 2021)
This article aims to study the development of the political participation of women in Algeria from the independence until the present day. It is done through analysing the constitutions, various legal laws, especially the constitution of 2008, and international conventions on women by showing the impact of political changes, such as the “democratic transition” that began in 1989 on women’s political participation. The results showed that although women have been assigned as ministers and leaders of political parties and the judicial system, in different periods, the problems and obstacles which are faced by Algerian women and their role in political life such as traditions and electoral laws on the line still exist and are to be highlighted in this study.